2010
DOI: 10.1115/1.4001759
|View full text |Cite
|
Sign up to set email alerts
|

Methanol-Tolerant Oxygen Reduction Reaction at Pt–Pd/C Alloy Nanocatalysts

Abstract: Carbon-supported platinum and Pt–Pd alloy electrocatalysts with different Pt/Pd atomic ratios were synthesized by a microemulsion method at room temperature (metal loading is 10 wt %). The Pt–Pd/C bimetallic catalysts showed a single-phase fcc structure and the mean particle size of Pt–Pd/C catalysts was found to be lower than that of Pt/C. The methanol-tolerant studies of the catalysts were carried out by activity evaluation of oxygen reduction reaction (ORR) on Pt–Pd catalysts using a rotating disk electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The durability of the cathode catalyst for the oxygen reduction reaction (ORR) is one of the primary roadblocks hindering the commercialization of proton exchange membrane fuel cells (PEMFC). , Currently, carbon black (i.e., Vulcan XC72 materials) supported Pt catalysts are the most commonly used, state-of-the-art catalysts for PEMFC. Unfortunately, the carbon supports do not meet the long-term durability requirements for PEMFC. For example, under fuel cell operating conditions, the Pt/C catalysts are subject to high electrode potential changes in the O 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The durability of the cathode catalyst for the oxygen reduction reaction (ORR) is one of the primary roadblocks hindering the commercialization of proton exchange membrane fuel cells (PEMFC). , Currently, carbon black (i.e., Vulcan XC72 materials) supported Pt catalysts are the most commonly used, state-of-the-art catalysts for PEMFC. Unfortunately, the carbon supports do not meet the long-term durability requirements for PEMFC. For example, under fuel cell operating conditions, the Pt/C catalysts are subject to high electrode potential changes in the O 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Pt/C catalyst with highly dispersed Pt nanoparticles (NPs, 2-5 nm) supported on carbon is widely employed as the state-of-the-art commercial catalyst. [6][7][8][9][10] The poor durability of the Pt/C catalyst is marked by a rapid and significant loss of platinum electrochemical surface area (ECSA) over time due to the corrosion of carbon support and Pt dissolution, Ostwald ripening, and aggregation during fuel cell operation. 11,12 The degradation of Pt/C catalysts is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, using Pd as the second metal in PtM/C catalyst was found not only to enhance the ORR activity but also to increase the catalyst's methanol tolerance. 259,260 Among various carbon-supported PtM nanoparticle alloy catalysts, core−shell structured alloy catalysts with M or PtM alloy as the core and Pt as the shell have been found to exhibit considerably higher performance for the ORR than pure Pt/C. Strasser's group 261,262 has synthesized a series of core−shell structured PtM/C (M = Co, Cu) catalysts with PtM alloy as the core and Pt as the shell through a dealloying process.…”
Section: Effect Of Particle Size On Orr Activitymentioning
confidence: 99%
“…Using electrochemical dealloying, Strasser's group also studied a series of PtM 3 /C systems with different metals as the second alloy elements (M = Cu, Co, and Ni). 259 They examined the composition of PtM 3 using EDS (energy dispersive spectroscopy), XPS (X-ray photoelectron spectroscopy), and ICP-MS (inductively coupled plasma-mass spectroscopy; see Table 8) and found that the dissolution of 3d metals resulted in compositional changes. The degree of dealloying of Pt−Co and Pt−Ni binary systems was lower than that of Pt−Cu compounds, as evidenced by the presence of around 15−20 at.…”
Section: Effect Of Composition On Orr Activitymentioning
confidence: 99%